GROWTH OF MATE TEA TREE SEEDLINGS FERTILIZED WITH N, P AND K - SANTIN, Delmar; BENEDETTI, Eliziane Luiza; BRONDANI, Gilvano Ebling; REISSMANN, Carlos Bruno; ORRUTÉA, Alessandro Góis; ROVEDA, Luís Fernando (Scientia Agraria, 2008)
The significant reduction of mate native populations areas has been impelling the search for seedlings of mate tea for new mate stands implantation. However, there are few studies related to adequate levels of N, P and K for the production of seedlings of mate tea. With the objective in evaluating the nitrogen, phosphorus and potassium doses on the initial growth of seedlings of mate tea tree an experiment were installed in a greenhouse it UFSM-RS. After five months under dormancy break the seeds were sown in a seed bed. In October 2004, the seedlings were transplanted for vases with 2 dm³ of soil, Argilic red-yellow. The experiments were carried out in blocks at random with eight treatments: T1-control, T2-100, T3-200, T4-300, T5-400, T6-500, T7-600 and T8-700 mg of the tested element kg-1 of soil (N, P and K). After 270 days of transplanting, total height (H), diameter of the collar (DC), fresh matter of the above ground part (MFPA), dry matter of the root (MSR), dry matter of the above ground part (MSPA) and total dry matter (MST), were analysed. The seedlings produced the best growth on the average dose of 447.5 mg kg-1 of P, for all analyzed variables. However, the same was not observed for treatments with N and K. Doses of N and K higher than 100 mg kg-1 substrate showed to be inadequate for mate tea tree seedlings productions.